(untitled) (PerCursos, 2022)
This article aims to address the relationship between migratory movements and the world of work. Its main objective is to analyze the legal protection of immigrant workers at national and international levels, from the perspective of fundamental human rights. It analyzes the International Convention for the Protection of the Rights of Migrant Workers and their Families of the ONU, as well as the paradigm shift introduced by the Migration Law (Law nº 13.445/17). In addition, it investigates the exercise of the right of access to the Labor Court by immigrants as an instrument for the enforcement of rights and how the labor judiciary has responded to the demands proposed by this population. Methodologically, the bibliographical review and the documental analysis of legal proceedings played a preponderant role. It was found that in addition to violations of basic rights, Haitian immigrants are routinely victims of racial discrimination in the workplace, featuring a strong relationship between xenophobia and racism, which requires the development of more effective actions to combat discriminatory practices.